The Liability of Curators for Share Capital Deposits: A Study on the Bankruptcy of PT Alam Galaxy as Debt - Sutomo, Alexander; C. Adam, Richard (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, a curator in bankruptcy proceedings should act transparently, accountably, and professionally so that all company assets, including share deposit funds, are managed in accordance with legal provisions without causing harm to any party. However, the reality shows deviations, as in the bankruptcy case of PT Alam Galaxy, where share deposit funds were converted into debt with inflated values, even involving alleged document forgery and creditor claim mark-ups. This study aims to analyze the curator’s liability for share deposit funds recognized as debt in the bankruptcy case of PT Alam Galaxy based on Decision Number 54/Pdt.Sus-PKPU/2021/PN Niaga Surabaya. In addition, it examines the legal implications of recognizing capital deposits as debt for the legal position of the company, creditors, and shareholders. The research employs a normative juridical method with statutory, case, and conceptual approaches, supported by analysis of official court documents, literature, and bankruptcy law principles. The findings indicate that curators are obliged to bear responsibility for negligence or actions that cause losses to the bankrupt estate as regulated under Article 72 of the Bankruptcy Law and may even be held personally liable under Article 1365 of the Civil Code. Furthermore, the recognition of share deposit funds as debt leads the company into insolvency, disrupts the corporate capital structure, and undermines legal protection for creditors and shareholders.